Alteration of chromatin states perturb the transcription regulation of gene during hydronephrosis - Wang, Xiao-Hui; Zhang, Shu-Feng; Wu, Hai-Ying; Gao, Jian; Wang, Lin; Yin, Yao; Wang, Xuhui (Frontiers in Genetics, 2025)
BackgroundGene expression is abnormal in disease compared to normal tissue same as the regulatory elements. Regulatory element binding with transcription factors managed transcription of gene, which usually require chromatin accessible.MethodsTo reveal potential epigenetic mechanism during hydronephrosis, we first used RNA-seq to finger out the disfunction genes during hydronephrosis, then combined with ATAC-seq, and BS-seq to reveal the related disfunction regulatory elements.ResultsFinally, we find that 860 differentially genes and 2429 dynamic chromatin open regions between normal and hydronephrosis tissue. Though, most of disfunction genes and regulatory elements significantly enriched in chronic kidney disease GO term, only small part of regulatory element target genes overlapped with truly disfunction genes. And we also find out an important gene OTUD6B, which overexpression in disease tissue is manipulated by distal regulatory element through chromatin loop, and confirm the importance of epigenetic mechanism in disease.ConclusionIn summary, we found many hub genes and potential therapeutic target during hydronephrosis, and also confirmed that epigenetic play important role in gene expression and relevant in disease progress.